A feminist teacher's account of her attempts to achieve the goals of feminist pedagogy. Issue 4 (7th June 2017) - McCusker, Geraldine
ABSTRACT: This paper aims to interrogate some of the processes and tensions I faced in establishing a feminist space in a higher education institution in the UK context. The students I worked with needed to develop an understanding of social justice concepts such as anti-discrimination and anti-oppression in order to progress from their undergraduate studies to a postgraduate professional qualification in social work. It was my contention that a feminist lens could support this understanding. The feminist space we established was informed by work in the field of feminist pedagogy, which supports the development of critical thinking that goes beyond the immediate learning context. Feminist pedagogy brings many rewards but also challenges and tensions, some of which I will explore in the paper. I will focus here on my efforts to establish and maintain this space, discussing what was achieved, and exploring the tensions involved when doing this in a neoliberal context, which as a depoliticised context, is a challenge to, and is challenged by, critical perspectives such as feminism.